Unveiling the notion of truth in Islam and postmodernism perspectives of International Islamic University Malaysia (IIUM) and Universitas Islam Negeri (UIN) Sunan Kalijaga - Al Giffari, Haekal Adha; Vikanza, Elsani; Harahap, Aidah Iman Sari; Syamsuar, Dafinanza Dafheri; Fidantyo, Muhammad Naufal (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2023)
The objective of this study is to compare the concept of truth between Islam and postmodernism which it will be responded by the academicians of International Islamic University Malaysia (IIUM) and Islamic State University Sunan Kalijaga (UIN Suka), leading to further comparison. Qualitative study with an in-depth interview approach will be employed in this study to gather the primary data while thematic analysis will be used to analyze and categorize the garnered information. Also, the results exhibit that all respondents identify the differences between Islam and postmodernism as the former is based on Quran and Sunnah while the latter subscribe relativism. Furthermore, the similarities expound that both articulate their intention and destination is to create a better world. Additionally, the academician of IIUM used frequently the word related to Islamic values while UIN Sunan Kalijaga's lecturers preferred to explain with contemporary and philosophical word. In conclusion, regardless of whether Islam and postmodernism, or the lecturer of IIUM and UIN Sunan Kalijaga, the similarities and differences are identified which those will strengthen the discipline.